A Note on Five Early Neolithic Sites in Inland Syria - van Liere, Willem J.
I. Introduction; II. Neolithic Variability of Inland Syria; III. The Sites: Sahi el Sahra, Springs of the Вarada, Saidnaya, Tell Ramad (Kattana) (Damascus Drainage Basin), Bouqras (Middle Euphrates).